2015
DOI: 10.1080/00071668.2015.1080814
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different formulations of α-tocopherol acetate (vitamin E) on growth performance, meat quality and antioxidant capacity in broiler chickens

Abstract: The objective of this study was to investigate and compare the effects of α-tocopherol acetate (vitamin E (VE)) and microencapsulated VE (MVE) on growth performance, meat quality and antioxidant capacity in broiler chickens. A total of 360 d-old broiler chicks were procured and randomly allocated into three groups with 6 replicates. Each replicate had 20 chickens. Chickens were fed with basal diets (CON group) or experimental diets supplemented with 20 mg/kg VE (VE group) or 20 mg/kg MVE (MVE group) for 42 d. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 44 publications
2
10
0
Order By: Relevance
“…The positive effects of the feed supplementation with vitamin E on the protective effects against lipid oxidation observed in this study were consistent with results of previous experiments (Voljč et al, 2013 ; Hu et al, 2015 ). Supplementation with vitamin E and the combination of antioxidants lowered the content of MDA in breast muscle.…”
Section: Discussionsupporting
confidence: 93%
“…The positive effects of the feed supplementation with vitamin E on the protective effects against lipid oxidation observed in this study were consistent with results of previous experiments (Voljč et al, 2013 ; Hu et al, 2015 ). Supplementation with vitamin E and the combination of antioxidants lowered the content of MDA in breast muscle.…”
Section: Discussionsupporting
confidence: 93%
“…Vitamin E is a major chain-breaking antioxidant and free radical scavenger, which constitutes a second line of defence for the prevention of lipid peroxidation. Diets supplemented with VE or MVE had a positive influence on stabilizing breast meat quality (Hu et al 2015;Zhang et al 2009).…”
Section: Total Phenolic Content and Antioxidant Activitymentioning
confidence: 97%
“…Improved feed efficiency of quail was reported by supplementation of vitamin C as an antioxidant that affected the utilization of dietary nutrients (Sahin & Kucuk 2003). Previous studies reported that dietary antioxidants, such as vitamin C, E, flavonoids, and phenolics, could reduce oxidative damage in animals which is generated by different stress sources (Brisibe et al 2009, Hu et al 2015. Therefore, the dietary supplementation of PPE, which contained natural antioxidant HTs, may improve feed efficiency by reducing oxidative damage in broilers fed diet fish oil.…”
Section: Broiler Performancementioning
confidence: 99%
See 1 more Smart Citation
“…The levels of alpha-tocopherol in the diets did not influence (p>0.05) the color (L*, a*, b*), pH, temperature, shear force, or weight loss by cooking of the breast muscle of chickens slaughtered at 42 days of age (Table 6). Hu et al (2015) compared the effects of α-tocopherol acetate and vitamin E, micro encapsulated on the production performance and meat quality of broiler chickens and did not observe effects on the levels of luminosity (L *), red (a *), yellow (b *), in the loss of weight by cooking and in the shear strength of the breast of broilers raised until 42 days of age. Divergent results were found by Hashizawa et al (2013), who evaluated the effect of vitamin E supplementation on the quality of breast meat from broilers raised under heat stress up to 38 days of age and observed an effect on red (a *) levels.…”
Section: Consistentmentioning
confidence: 99%